Tecendo espirais, entrelaçando e partilhando experiências de vida-formação: tutores da educação a distância e seus percursos formativos (construindo um projeto de/para si) - Souza, Laura Rocha Lima de (2023)
This dissertation aims to understand how a training process for a distance education tutor, based on their memories narrated in a training memoir, constitutes a project from/to the self. It is highlighted the importance of of registering the narratives of the tutors’ life history, sharing their experience and objectifying a life-training project, as such, it is noticed that in the research training we find a place of speech and encouragement, to allow others to narrated their training practices and life experiences, building a set of sources which establishes a scientific trajectory, that follows another method and epistemology. With that in mind, in order to list this study in a logical manner, we have organized this dissertation in chapters, on which the discussions are done within a theoretical scope about the training of the educational professionals on the field of research-formation. This perspective has contributed to a theoretical framework of the investigations in the Education field through an (auto)biographical approach and other tendencies. It was necessary to investigate and get to know the distance education tutor’s profile and what role is attributed to them in education. The methodology adopted in this paper is narrative research based on an (auto)biographical approach, since, by its own nature, it allows the participants to remember subjects which give meaning to their personal and professional lives. As such, the subjects/authors can report and share their experiences by a training device. A proposal of the analysis made through Paul Ricoues’s theory about the hermeneutic circle was idealized, as a basilar and guiding trajectory towards the strategic analysis. This strategy focuses on establishing relations that intertwine the narratives and certain fundamental dimensions of our connection with the world. By doing this, the happenings that compose the narrative plot of the training memorial are selected by the subject/author as important and give meaning to the training. While investigating, the preparation of the training memorial was made in distinct moments of the subject/author’s narrative pre-configures, configures and reconfigures their experiences, giving them meaning. In this process, we have proposed reflections and interpretations of what was narrated, based on the idea that the subject/author establishes a structure between life and training, between the professional and the personal, building a life-training project, reconfiguring the future based on the knowledge from/to the self.